How to detect the manipulation of financial statements in EU financial incentives in Portugal - Fernandes, S. Ribeiro; Laureano, Raul M. S.; Laureano, L. (48th World Continuous Auditing and Reporting Symposium, 2020)
Portugal has been receiving funds from the EU for 33 years to help develop its economy. However, there are still those who question the success of the EU funds received. Indeed, firms try by all means to have their investment projects approved. This work predicts the propensity of firms to manipulate their financial statements, using the Beneish's M-Score and classification techniques. The results help public organizations identify which projects are more prone of being unsuccessful and thus alert for the need of a better scrutinization of these projects and the firms behind them.